The Effect of Family Social Support and Self Esteem in Improving the Resilience of Tuberculosis Patients - Intan Pandini; Aisyah Lahdji; Nina Anggraeni Noviasari; Merry Tiyas Anggraini (Universitas Muhammadiyah Semarang, 2022)
An individual's ability to survive determines the success of treatment is called resilience. Family social support and self-esteem are factors that affect resilience and play an important role in the lives of sufferers who are determined to recover. This study aims to find out the relationship of family social support and self-esteem with the resilience of TB sufferers in the working area of Bangetayu Health Center. This research used analytical observational methods with a cross-sectional design, the total sample was 30 respondents with a total sampling technique. The instruments used are medical records, demographic data questionnaires, MSPSS questionnaires, RSES questionnaires, and resilience questionnaires and then data processed with spearman rho tests. Statistical test results found a relationship between family social support and resilience showed a value of ρ = 0,000 (ρ ≤ 0,05) and rho (r) = 0,809 which means there is a very strong correlation, as well as a relationship between self-esteem and resilience that shows the value of ρ = 0,000 (ρ ≤ 0,05) and rho value (r) = 0,787, then there is a strong correlation between variables and accompanied by a positive pattern. Thus, there is a significant relationship and a positive direction of the relationship. This study shows that the higher the family social support and self-esteem, the higher the resilience of TB sufferers.